Chemical Characteristics and SEM Analysis of Compost from Cassava Peel Waste and Cow Manure: Production by Pendawa I Farmer Group, Candi Rejo Village - Sebayang, Nur Ulina Warnisyah; Akasah, Wida; Manurung, Vindy Rilani; Sinamo, Karina Nola; Perangin-angin, Gilang Aulia; Lesmana, Alghi Fahry; Rahma, Kirana Aulia (Talenta Publisher, 2023)
Cassava peel waste and cow dung in the Pendawa I Farmer Group, Candi Rejo Village, Sibiru-biru District, are managed into compost which can be reused for cultivated plants. However, it is necessary to analyze the chemical characteristics of the compost produced by good compost according to SNI 19-7030-2004. The purpose of this activity is to determine the chemical characteristics and SEM analysis of compost made from cassava skin waste and cow dung produced by the Pendawa I Farmer Group. carried out for 4 weeks. The materials used were 100 kg of cassava skin waste, 200 kg of cow dung, water, molasses, and enough EM4 as an activator. Parameters observed included compost pH, total N (%), total P2O5 (%), K2O (%), C-organic (%), CEC (me/100), compost moisture content (%), C/N ratio, and micronutrients which include Ca (%), Mg (%), Fe (%), Mn (%), Cu (ppm) and Zn (ppm). As well as SEM (Scanning Electron Microscope) analysis with 2500x magnification. The results of compost analysis show that the final chemical characteristics of the compost have pH (6.50 : neutral), N-total (1.37% : very high), Total P2O5 (0.48% : very high), K2O (0.25% : high), C-organic ( 25.06% : very high), CEC (125.05 me/100 : very high), compost moisture content (20.15%), C/N ratio (18.29), Ca (0.10%), Mg (0.30%), Fe (0.97% ), Mn (0.09%), Cu (7.43 ppm) and Zn (46.64 ppm). Based on the results of laboratory analysis, the results of the chemical analysis of the compost are by following SNI 19-7030-2004 so that farmers in the Pendawa I Farmer Group can continue to produce the compost.